Subjecting pandemic sport to a sociological procedure - Rowe, D. (Journal of Sociology, 2020)
The Covid-19 global pandemic posed a particularly acute problem for sport. Although there was massive sectoral disruption in areas like higher education, music, and tourism, sport is unusually dependent on commercial media-financed, impossible-to-repeat live events performed before large co-present crowds that form a key part of the spectacle for the many times larger, distant audiences using an expanding range of screens. Covid-19 exposed the inner workings of sport as a machine that could be disabled by its own global interdependency. The compulsive generation of inequalities of class, `race`/ethnicity, gender, sexuality, age, ability, space, and so on resulting from the advanced commoditisation and consequent hierarchisation of contemporary global sport, created the structural imbalance and vulnerability that Covid-19 has mercilessly punished. This article applies a sociological analysis to sport before, during and after the pandemic, arguing that an emphasis on the relationships between human rights and cultural citizenship is required to improve the social institution of sport. It argues that if sociology does not play a key role in reforming sport after Covid-19, then it will have lost the moral compass that first guided the discipline in early modernity when the institution of sport emerged.